Bifunctional heterogeneous catalysts derived from the coordination of adenosine monophosphate to Sn(iv) for effective conversion of sucrose to 5-hydroxymethylfurfural. Issue 2 (15th December 2021) - Wang, Chenyu; Jiao, Lutong; Meng, Han; Ji, Peijun
Abstract : Adenosine 5′-monophosphate (AMP) with multiple functional groups was used for the synthesis of Sn-AMPs. The Sn-AMPs have both Brønsted acid and Lewis acid sites. The Sn-AMPs demonstrated a superior capability for catalyzing sugars into HMF. Abstract : Adenosine 5′-monophosphate (AMP) with multiple functional groups can bind to various metal ions. In this work, AMP has been used as a ligand to coordinate Sn(iv ) for the synthesis of porous coordination polymers (Sn-AMPs). The Sn-AMPs have both Brønsted acid (BA) and Lewis acid (LA) sites and have been used as bifunctional heterogeneous catalysts for catalyzing the conversion of sucrose to 5-hydroxymethylfurfural (HMF), involving hydrolysis of sucrose to glucose and fructose, isomerization of glucose to fructose, and dehydration of fructose to HMF. The protonated N1 and OH–P of the coordinated AMP can form hydrogen bonds with glucose and fructose. This can promote the conversion of the sugars. Sn-AMP has exhibited a superior capability for the conversion of biomass-derived sugars into HMF. The HMF yields of 76.1%, 67.5% and 62.9% were achieved from fructose, glucose, and sucrose, respectively.